Overview of indicators of information and digital resources of the Federal Tax Service that characterize the small businesses activities - M. V. Karp; A. V. Zakharova; M. V. Tipalina; L. S. Samodelko (Вестник университета)
Entrepreneurship is an integral part of the market economy. However, only recently it has been possible to analyse this cluster online. The purpose of the research paper is a qualitative analysis of indicators formed by the Federal Tax Service of Russia to characterize the activities of small and medium-sized businesses. The article presents the results of a review of the indicators of information and digital resources of the Federal Tax Service of Russia that characterize the activities of small businesses: the unified register of small and medium – sized businesses; the unified register of small and medium-sized businesses – recipients of support; the unified state register of taxpayers; the state information register of accounting (financial) reporting; the “Transparent Business” service. It is concluded that the information and statistical databases of the Federal Tax Service of Russia have a significant potential for partial formation of statistical reporting data of small and medium-sized businesses, and are also acceptable for economic and statistical analysis of the activities of both a specific entity and a group of entities.